Analisis Pengembangan UMKM Melalui Usaha Budidaya Madu Akasia dalam Meningkatkan Ekonomi Petani di Kecamatan Bandar Laksamana Kabupaten Bengkalis - Zulpan; Hendri, Zul (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to analyze the development of Micro, Small, and Medium Enterprises (MSMEs) through acacia honey cultivation as a means to improve the economic conditions of farmers in Bandar Laksamana District, Bengkalis Regency. Acacia honey farming is seen as a promising form of business diversification for farmers to increase their income and strengthen local economic resilience. This research employs a qualitative descriptive approach with data collection techniques including observation, in-depth interviews, and documentation. The findings indicate that the development of MSMEs through acacia honey cultivation significantly contributes to increasing farmers' income, creating new employment opportunities, and strengthening community-based business networks. However, this development still faces challenges such as limited access to markets, capital, and technical training. Therefore, active involvement from local governments and supporting institutions is needed in providing training, financial assistance, and broader market access so that acacia honey farming can grow sustainably and become a driving force for farmers' economic development in the region.